Entrepreneurship in tourism and hospitality industry - Arenas, Chester Dave G. (Manila, Philippines : Edric Publishing House, 2020)
A global perspective gives a new and definitive overview of the vital role and effective practice of entrepreneurship.
CHAPTER 1. Introduction to entrepreneurship -- 2. The role of entrepreneurship in hospitality and tourism industry -- 3. Developing a business plan -- 4. Market analysis -- 5. Marketing strategies -- 6. Starting and operating a business -- 7. Introduction to bookkeeping -- 8. Financial statement analysis.
Includes bibliographical references.
Keywords: HOSPITALITY INDUSTRY -- MANAGEMENT